УМУМКАСБИЙ ФАНЛАРДАН ЎҚУВ МАШҒУЛОТЛАРИНИ РАҚАМЛИ ТАЪЛИМ ТЕХНОЛОГИЯЛАРИ АСОСИДА ТАШКИЛ ЭТИШ - Қурбонов, Ғ.Ғ. (SCIENCE and SOCIETY, 2022)
This article analyzes the role of a mobile application in the field of education and ways to implement it, developed in the subject “Numerical Methods” in the block of general education sciences. A scientifically based approach to the implementation of the developed mobile application in the educational process has been formed and the corresponding conclusions have been drawn.